The Nightmare Disorder Index: development and initial validation in a sample of nurses. Issue 5 (27th November 2020) - Dietch, Jessica R; Taylor, Daniel J; Pruiksma, Kristi; Wardle-Pinkston, Sophie; Slavish, Danica C; Messman, Brett; Estevez, Rosemary; Ruggero, Camilo J; Kelly, Kimberly
Abstract: Study Objectives: Nurses are a group at high risk for nightmares, yet little is known about the rate of nightmare disorder and associated psychosocial factors in this group in part attributable to the lack of a self-report questionnaire to assess DSM-5 criteria for nightmare disorder. Aims of the current study were to (1) report on development and initial validity of a self-report measure of DSM-5 nightmare disorder, and (2) examine the rate and associated factors of nightmare disorder among nurses. Methods: Nurses ( N = 460) completed baseline measures online including Nightmare Disorder Index (NDI), psychosocial and demographic questionnaires. A subset ( n = 400) completed 14 days of sleep diaries and actigraphy. Results: NDI demonstrated satisfactory psychometric characteristics as indicated by good internal consistency ( α = 0.80), medium inter-item correlations ( r = 0.50), medium to large item-total ( r = 0.55–0.85) and convergent correlations (0.32–0.45), and small to medium discriminant correlations (–0.12–0.33). Per NDI, 48.7% of nurses reported no nightmares in the past month, 43.9% met partial/subthreshold criteria and 7.4% met full criteria for probable nightmare disorder. Nurses with nightmare disorder demonstrated significantly poorer psychosocial functioning (i.e. posttraumatic stress, depression, anxiety, stress) than those with subthreshold nightmare symptoms, who had poorer functioning than those with no nightmares. Conclusions: NDI is an efficient and valid self-report assessment of nightmare disorder. Nurses have high rates of nightmares and nightmare disorder which are associated with poorer psychosocial functioning. We recommend increased nightmare screening particularly for high-risk populations such as healthcare workers.